Equilibrium securitization with diverse beliefs. Issue 1 (27th January 2022) - Ellis, Andrew; Piccione, Michele; Zhang, Shengxing
Abstract : We study the effects of diverse beliefs on equilibrium securitization under risk neutrality. We provide a simple characterization of the optimal securities. Pooling and tranching of assets emerges in equilibrium as a consequence of the traders' diverse beliefs about asset returns. The issuer of securities tranches the asset pool, and traders sort among the tranches according to their beliefs. We show how the traders' disagreement about the correlation of asset returns is a key factor in determining which assets are pooled.